Reliability Issues and Solutions in Flexible Electronics Under Mechanical Fatigue - Yi, Seol-Min; Choi, In-Suk; Kim, Byoung-Joon; Joo, Young-Chang (KOREAN INST METALS MATERIALS, 2018)
Flexible devices are of significant interest due to their potential expansion of the application of smart devices into various fields, such as energy harvesting, biological applications and consumer electronics. Due to the mechanically dynamic operations of flexible electronics, their mechanical reliability must be thoroughly investigated to understand their failure mechanisms and lifetimes. Reliability issue caused by bending fatigue, one of the typical operational limitations of flexible electronics, has been studied using various test methodologies; however, electromechanical evaluations which are essential to assess the reliability of electronic devices for flexible applications had not been investigated because the testing method was not established. By employing the in situ bending fatigue test, we has studied the failure mechanism for various conditions and parameters, such as bending strain, fatigue area, film thickness, and lateral dimensions. Moreover, various methods for improving the bending reliability have been developed based on the failure mechanism. Nanostructures such as holes, pores, wires and composites of nanoparticles and nanotubes have been suggested for better reliability. Flexible devices were also investigated to find the potential failures initiated by complex structures under bending fatigue strain. In this review, the recent advances in test methodology, mechanism studies, and practical applications are introduced. Additionally, perspectives including the future advance to stretchable electronics are discussed based on the current achievements in research.